Determination of the Organoleptic Quality of Hard Dough Biscuits during the Shelf Life by Chemical Analysis - Senarathna, H.W.U.N.; Navaratne, S.B. (Creative Commons Attribution-ShareAlike 4.0 International License, 2017)
Attached
Keywords: Free fatty acids, Hard dough biscuits, Organoleptic properties, Peroxide value, Total carbonyl content.